Essential business grammar & practice - Duckworth, Michael (Oxford ; New York : Oxford University Press, 2006)
Suitable for lower-level learners, this title offers clear explanations of grammar points, along with practice activities. Based on authentic source material, it provides contexts relevant to adult professional learners' needs. Containing progress tests, it also includes short end-of-unit sections allowing students to personalise key grammar
Elementary to pre-intermediate. Includes index.
BSBA
Keywords: English language -- Business English -- Textbooks for foreign speakers; English language -- Business English -- Problems, exercises, etc; English language -- Grammar -- Textbooks for foreign speakers